2006
DOI: 10.1111/j.1572-0241.2006.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Association Between Isotretinoin and Inflammatory Bowel Disease

Abstract: In a subgroup of patients, isotretinoin might serve as a trigger for IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 14 publications
4
57
1
2
Order By: Relevance
“…Some cases demonstrate remission and flares of inflammatory bowel disease on de-challenge and re-challenge. 39 However, patients with known ulcerative colitis have been treated successfully with isotretinoin without exacerbation of their condition, 40,41 and it appears that, at least in some European countries, the majority of patients with inflammatory bowel disease have not been exposed to isotretinoin. 42 The establishment of causality is clouded by the vagueness of the initial symptoms of inflammatory bowel disease and the fact that the average age of onset is during the young adult years.…”
Section: Gastrointestinal Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases demonstrate remission and flares of inflammatory bowel disease on de-challenge and re-challenge. 39 However, patients with known ulcerative colitis have been treated successfully with isotretinoin without exacerbation of their condition, 40,41 and it appears that, at least in some European countries, the majority of patients with inflammatory bowel disease have not been exposed to isotretinoin. 42 The establishment of causality is clouded by the vagueness of the initial symptoms of inflammatory bowel disease and the fact that the average age of onset is during the young adult years.…”
Section: Gastrointestinal Effectsmentioning
confidence: 99%
“…39,40 These include the development of symptoms in both patients on isotretinoin therapy and in the years after therapy. Because the cause of inflammatory bowel disease is not known, it is difficult to know what level of concern to place on reports of patients who develop symptoms that are not temporally related to the course of isotretinoin.…”
Section: Gastrointestinal Effectsmentioning
confidence: 99%
“…Many studies concerning the relationship between isotretinoin and IBD have been conducted, but there is no concordance between their results (14). Reddy et al concluded that in a subgroup of patients, isotretinoin might serve as a trigger for IBD (15). Crockett et al in their first study in 2009 mentioned that evidence was insufficient to confirm or refute a causal association, while in their second study they claimed that ulcerative colitis but not Crohn disease was associated with previous isotretinoin exposure (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Еще од-но осложнение, внимание к которому привлечено относительно недавно, -связь изотретиноина и воспалительных заболеваний кишечника [50]. В от-чете FDA о побочных эффектах изотретиноина за 1997-2002 гг.…”
Section: клиническая дерматология и венерология 6 2015unclassified